2023
DOI: 10.1021/acs.langmuir.3c00621
|View full text |Cite
|
Sign up to set email alerts
|

Designing the Macroporous Structure of Three-Way Catalyst Particles: The Influence of Template Concentration on Framework Thickness and Mass Transfer

Abstract: Mass transfer is an essential process that can extend the performance and utilization of nanoporous materials in various applications. Therefore, improving mass transfer in nanoporous materials has always attracted much interest, and macroporous structures are currently being studied to enhance mass transfer performance. The introduction of macroporous structures into three-way catalysts (TWC), which are widely utilized to control the emission of polluted gases from vehicles, provides the potential to enhance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…In contrast, the superior catalytic performance of the macroporous TWC particles is attributed to their convective diffusion property, where macropores are preferable for reactant transportation within the structure (Figure 7c). 44 The improved convective diffusion within the particles facilitates contact between the reactants and the interior catalyst surface, thereby enhancing the overall catalytic performance. Therefore, producing macroporous catalyst particles shows great potential for enhancing catalytic performance by improving the mass transfer efficiency within the particles.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, the superior catalytic performance of the macroporous TWC particles is attributed to their convective diffusion property, where macropores are preferable for reactant transportation within the structure (Figure 7c). 44 The improved convective diffusion within the particles facilitates contact between the reactants and the interior catalyst surface, thereby enhancing the overall catalytic performance. Therefore, producing macroporous catalyst particles shows great potential for enhancing catalytic performance by improving the mass transfer efficiency within the particles.…”
Section: Resultsmentioning
confidence: 99%
“…34,42−45 Recently, Le et al efficaciously synthesized macroporous TWC particles via a straightforward aerosol process with the assistance of template particles. 44,45 This work demonstrated that the hierarchically ordered macroporous structure exhibits a higher mass transfer efficiency than the aggregate structure due to the facility of macropores. Therefore, macroporous TWC particles hold significant promise for achieving excellent catalytic performance owing to their high mass transfer efficiency within the structure.…”
Section: ■ Introductionmentioning
confidence: 84%
See 3 more Smart Citations